2020
DOI: 10.2147/phmt.s257804
|View full text |Cite
|
Sign up to set email alerts
|

<p>Determinants of Delayed Treatment-Seeking for Childhood Diarrheal Diseases in Southwest Ethiopia: A Case–Control Study</p>

Abstract: Background: Although there are low cost and effective interventions to prevent and treat diarrhea, it is one of the leading causes of morbidity and mortality among under-five children in developing countries. Deaths from diarrheal diseases are largely due to lack of prompt seeking of medical care. This study aimed to identify determinants of delayed treatmentseeking for diarrheal diseases among under-five children in Southwest Ethiopia. Methods: Unmatched case-control study was conducted among 324 under-five c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Infant and children are more likely to die due to lack of safe water and sanitation, along with poor hygiene practices, that result in deteriorative synergy that leads to diarrheal disease [ 58 ]. Health seeking behavior such as poor early sough of health care, less measure to diarrhea disease management including oral rehydration therapy (ORT) for rehydration were responsible for diarrhea-related mortality [ 59 ]. Other deaths due to severe malnutrition, Measles, Pulmonary tuberculosis and HIV/AIDS appeared to be tribulation of infant’s survival on the basis of the present study result.…”
Section: Discussionmentioning
confidence: 99%
“…Infant and children are more likely to die due to lack of safe water and sanitation, along with poor hygiene practices, that result in deteriorative synergy that leads to diarrheal disease [ 58 ]. Health seeking behavior such as poor early sough of health care, less measure to diarrhea disease management including oral rehydration therapy (ORT) for rehydration were responsible for diarrhea-related mortality [ 59 ]. Other deaths due to severe malnutrition, Measles, Pulmonary tuberculosis and HIV/AIDS appeared to be tribulation of infant’s survival on the basis of the present study result.…”
Section: Discussionmentioning
confidence: 99%
“…Males were more likely to suffer from FBDs, as men were generally more adventurous than women when making irrational decisions (Shan et al, 2019). Children under six were more likely to suffer FBDs, as mentioned in the previous study (Havelaar et al, 2015), due to their lower immunity and the absence of health education.…”
Section: Discussionmentioning
confidence: 67%
“…The research results showed that the convenience of therapy significantly impacted how patients seek medical care 35. The distance between the residence and the medical institution could affect patients’ medical decision-making 36. Limited medical resources in rural areas could easily lead to misdiagnosis and delays in seeking medical care 37.…”
Section: Discussionmentioning
confidence: 99%
“…35 The distance between the residence and the medical institution could affect patients’ medical decision-making. 36 Limited medical resources in rural areas could easily lead to misdiagnosis and delays in seeking medical care. 37 Therefore, more attention should be paid to areas with little or lacking high-quality medical resources.…”
Section: Discussionmentioning
confidence: 99%